IDENTIFICATION AND INVENTORY OF CASSAVA (Manihot esculenta Crantz) IN NORTH SUMATERA - Emmy Harso Kardhinata; Edison Purba; Dwi Suryanto; Herla Rusmarilin (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2020)
The study of identification and inventory of cassava accessions was done from August to September 2014 in four districts based on their potential as a center for cassava cultivation, namely Simalungun, Serdang Bedagai, Deli Serdang, Langkat Regency representing the lowlands and Simalungun and Karo Regency representing the highlands. Each district was selected 3 subdistricts and each subdistrict was surveyed 3 villages randomly through the accidental sampling method. Guidance on identifying morphological characters was used by reference from Fukuda, et al. (2010) by giving a score for each character observed. The results of the study obtained 8 genotypes with their respective codes and local names; 1) Sawit (G1), 2) Lampung (G2), 3) Merah (G3), 4) Adira-1 (G4), 5) Kalimantan (G5), 6) Malaysia (G6), 7) Roti (G7) and 8) Klanting (G8). The most common genotype found in the location were Malaysia and Adira-1, while the rarest was Merah. The yield potential at the age of 10 months were Sawit (26,9–30,1 tons/ha), Lampung (29,6–52,6 tons/ha), Merah (54–61,6tons/ha), Adira-1 (34,8–55,0 tons/ha),  Kalimantan (15,8–64,2 tons/ha), Malaysia (32,9–64,3 tons/ha), , Roti (24,7–55,5 tons/ha), and Klanting (327,4–49,8 tons/ha).